2022
DOI: 10.3389/fphar.2022.933070
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Huangqin Decoction Combined Treatment With Radix Actinidiae chinensis on DSS and AOM-Induced Colorectal Cancer

Abstract: Objective: To demonstrate the effectiveness of Huangqin decoction (Huangqin Tang in Chinese, HQT) combined with Radix Actinidiae chinensis (Tengligen in Chinese, TLG) under the guidance of “dampness–heat theory” in preventing and treating colorectal cancer (CRC) with dampness–heat accumulation and to preliminarily reveal its mechanism.Methods: The mice model of CRC was established by intraperitoneal injection of AOM combined with consumption of 2.5% DSS solution, and celecoxib, HQT, TLG, and their combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Desulfobacterota and Proteobacteria have been reported to be able to accelerate the progression of inflammatory diseases by activating inflammatory vesicle signaling pathways [24], and M-18C was able to reduce the abundance of Desulfobacterota and Proteobacteria in the intestinal tract of AKI mice. There is evidence that Deferribacterota and Mucispirillum are strongly associated with intestinal inflammation and the risk of kidney disease [25][26][27][28], whereas in our experiments, we found that Deferribacterota abundance was elevated in the intestinal tracts of AKI mice, and M-18C intervention significantly reduced Deferribacterota abundance. Wei et al demonstrated that the abundance of Tuzzerella was positively correlated with urea nitrogen, reactive oxygen species, and IL-1β in the serum of hyperuricemic mice [29,30], and M-18C was able to reduce the abundance of Tuzzerella in the intestines of AKI mice.…”
Section: Discussioncontrasting
confidence: 84%
“…Desulfobacterota and Proteobacteria have been reported to be able to accelerate the progression of inflammatory diseases by activating inflammatory vesicle signaling pathways [24], and M-18C was able to reduce the abundance of Desulfobacterota and Proteobacteria in the intestinal tract of AKI mice. There is evidence that Deferribacterota and Mucispirillum are strongly associated with intestinal inflammation and the risk of kidney disease [25][26][27][28], whereas in our experiments, we found that Deferribacterota abundance was elevated in the intestinal tracts of AKI mice, and M-18C intervention significantly reduced Deferribacterota abundance. Wei et al demonstrated that the abundance of Tuzzerella was positively correlated with urea nitrogen, reactive oxygen species, and IL-1β in the serum of hyperuricemic mice [29,30], and M-18C was able to reduce the abundance of Tuzzerella in the intestines of AKI mice.…”
Section: Discussioncontrasting
confidence: 84%
“…Here, we further observed that similar to mesalazine, HQD exhibited an antitumor effect on mice induced with CAC. Although HQD has been shown to effectively inhibit DSS-induced colitis alone or by synergizing with Radix Actinidiae chinensis , this main function was associated with altering the composition of the intestinal flora and modifying the proportion of T-cell subsets in colorectal lymphoid tissues (Huang et al 2022a , b ). Therefore, the immunoregulatory function of HQD needs to be further explored and verified.…”
Section: Discussionmentioning
confidence: 99%